Growth and survival of the hatchery juveniles of pacific oyster Crassostrea gigas (Thunberg, 1793) in Peter the Great Bay - A. S. Tabelskaya; G. S. Gavrilova (Известия ТИНРО, 2021)
Growth and survival rates of juveniles of pacific oyster Crassostrea gigas are estimated for the first time in conditions of Peter the Great Bay (Japan Sea). The data were collected at artificial hatchery in the Aquaculture Center located on Popov Island in 2019. The juveniles were settled and reared on two types of substrate: 1) perforated plastic plates with the diameter of 30 cm (area 7.1 dm2), and 2) scallop shells with the height about 10 cm (average area 0.8 dm2) mounted in the western Peter the Great Bay (Voevoda Bay) in September 2019. Before placing in this site, the average height of the juveniles’ shells did not exceed 7 mm. In July 2020, after the 9-month exposure of the collectors with spat in the Voevoda Bay, the height increased in 12–18 times and reached 55–90 mm on the substrate 1 and 25–65 mm on the substrate 2. Then the oysters reared on the substrate 1 were replaced from the plastic plates to the cage shelves and the cages were moved to the Stark Strait. Difference in the growth rate became more apparent in September 2020, when the height of shells settled on the plastic plates reached 67 mm, on average (73 % in the range 50–85 mm) and for the shells settled on the scallops — 32 mm, on average (72 % in the range 20–45 mm). The shell height increased to 76.6 and 52.4 mm, respectively, to the end of October 2020. Finally, about 59 % of the oysters reared on the substrate 1 and cage shelves and 9 % of the oysters reared on the substrate 2 reached the commercial size (80–100 mm). Their survival in the period from mid-October 2019 to July 2020 is estimated as 46.9 % (28.8–98.2 %) for the substrate 1 and 33.5 % (4.0–78.3 %) for the substrate 2. On the substrate 1, survival of the mollusks attached to lower surface of the plates was twice higher. The survival had a tendency to decrease with increasing of the juveniles density. The experiment showed good viability for artificially hatched juveniles of pacific oyster in conditions of Peter the Great Bay. Their growth in the Voevoda Bay and the Stark Strait, with necessary technological measures, as replacing, thinning, and substrate cleaning from fouling, allows to produce oysters with the commercial size.